2020
DOI: 10.1371/journal.pone.0230422
|View full text |Cite
|
Sign up to set email alerts
|

Loci associated with conception rate in crossbred beef heifers

Abstract: The inability of beef cattle to maintain full term pregnancies has become an economic concern for the beef industry. Herd management and nutritional improvements have alleviated environmental impacts on embryonic and fetal loss, yet additional gains can be made through genomic selection. The objectives of this study were to identify loci and gene-sets in crossbred beef heifers associated with the number of services required to become pregnant (TBRD) and heifer conception rate at first service (HCR1). Heifers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This set of genes was involved in the catalysis of redox reactions, which have been associated with oxidative stressors having an impact on successful gestation. However, no loci were associated or any amplified gene set in the rate of conception at first service (Oliver et al, 2020). Furthermore, GST, GSH and GPx are essential indicators for evaluating the antioxidant system in plasma and they complement each other as they are dependent on glutathione.…”
Section: Articlementioning
confidence: 96%
See 1 more Smart Citation
“…This set of genes was involved in the catalysis of redox reactions, which have been associated with oxidative stressors having an impact on successful gestation. However, no loci were associated or any amplified gene set in the rate of conception at first service (Oliver et al, 2020). Furthermore, GST, GSH and GPx are essential indicators for evaluating the antioxidant system in plasma and they complement each other as they are dependent on glutathione.…”
Section: Articlementioning
confidence: 96%
“…Celi et al (2012) suggested that changes in plasma biomarkers of oxidative stress could not quantitatively reflect the modifications due to stress in reproductive tissues. Recently, Oliver et al (2020) identified in beef heifers a set of genes that are expressed in the endometrium of heifers, by acting on the increase in oxidoreductase activity with the number of services required for become pregnant. This set of genes was involved in the catalysis of redox reactions, which have been associated with oxidative stressors having an impact on successful gestation.…”
Section: Articlementioning
confidence: 99%
“…There have been several studies reporting use of GWAS to identify quantitative trait loci (QTLs) for fertility traits of beef cattle. Among these studies are GWAS for age at first calving [ 16 – 18 ], pregnancy to AI after estrous synchronization [ 10 ] or after fixed-time AI [ 12 ], pregnancy outcome at the end of the breeding season [ 11 ], conception rate and number of services required for pregnancy [ 19 , 20 ], rebreeding success after calving [ 21 ], and fertility classification following serial embryo transfers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%